Intercropping with the potential cadmium hyperaccumulator Solanum photeinocarpum, and its post‐grafting generations, decrease cadmium uptake and promote growth of cherry. Issue 2 (6th October 2022) - Xiao, Yunying; Zhou, Lianying; Liu, Linxi; Liao, Qiuyu; Li, Wanzhi; Lin, Lijin
Abstract: Cadmium (Cd)‐contaminated soil has affected the fruit production safety. To decrease the Cd accumulation in the fruits, the effects of intercropping with the potential Cd‐hyperaccumulator Solanum photeinocarpum and its post‐grafting generations on the Cd uptake in cherry ( Cerasus pseudocerasus ) were studied by the pot experiments. Intercropping increased the biomass of cherry seedlings to some extent, and decreased the biomass of S. photeinocarpum and its post‐grafting generations. Intercropping decreased the Cd contents in cherry seedlings, and increased the Cd contents in S. photeinocarpum and its post‐grafting generations. Compared with their respective monoculture, intercropping decreased the shoot Cd content in cherry seedlings by 31.37%–60.70%, and increased the shoot Cd contents in S. photeinocarpum its post‐grafting generations by 18.50%–28.76%. In addition, intercropping also decreased the root‐to‐shoot Cd translocations in both plant species, and decreased the Cd content in the branches and fruits of fruiting cherry trees and the Cd extractions of S. photeinocarpum and its post‐grafting generations. Therefore, intercropping with S. photeinocarpum and its post‐grafting generations can be used to reduce Cd accumulation in cherry for fruit production safety.